Relation between typological characteristics of nervous system and high sport achieving of wrestlers - Chernenko, N.; Lyzohub, V.; Korobeynikov, G.; Potop, V.; Syvash, I.; Korobeynikova, L.; Korobeinikova, I.; Mishchenko, V.; Kostuchenko, V. (Journal of Physical Education and Sport, 2020)
Purpose: was to clarify the role of individual-typological characteristics of the central nervous system for achieving of high results in the Greco-Roman wrestling. Material: The 2 groups of Greco-Roman wrestling were examined. The first group - 27 elite wrestlers (age 18-27), members of the National Team of Ukraine who having sports experience from 5 years and more. The second group 37 young wrestlers age 13-15. The third group (control) contains 13 couples of monozygotic (MH) and 18 - dizygotic (DZ) twins. They were not athletes. Methods of genetics, research of typological characteristics of the central nervous system: functional mobility (FMNS), strength (SNP), poise (PNP) of nervous processes and time of central processing of information, video recording and analysis of technical methods of wrestlers and mathematical statistics was used. Results. The links between genetically determined typological characteristics of the central nervous system and success of the Greco-Roman wrestling was found. Hereditary dependence of functional mobility and the relative advantage of the genotype - strength, poise of nervous processes and time of central processing of information is proved. Sensomotor characteristics did not reveal any dependence on genetic factors. The expressed dependence of the indexes of technological skills and the effectiveness of the competitive performance of wrestlers on their individual features that resulting from genetically was established. This index was functional mobility. The wrestlers, who had better indexes of the typological characteristics of the central nervous system, were characterized by higher level assessments of technological skills and conduct of the fight. Conclusions. Typological characteristics of the central nervous system - functional mobility, along with technical preparedness, - are recommended as highly genetically determined criteria for assessing the prospects of wrestlers.